PERLINDUNGAN HAK-HAK PEREMPUAN PASCA PERCERAIAN (STUDI TERHADAP PUTUSAN PENGADILAN AGAMA PALOPO) - Anita Marwing (Palita: Journal of Social Religion Research, 2016)
This article aims to determine the women rights in Islam, in post-divorce and in knowing the analysis of judges decision in Palopo Religious Court regarding the women rights after divorce. The findings showed that the judge's decision regarding the rights of women were concluded as follows; 1) the contested or talak divorce cases by verdict judgment did not cover the wives rights in which judges presumption should not decide the case on the outside of the charge materials (ultra-petition). So that, the judge did not dare to assign or guarantee the women rights legally after divorcing such as Mut'a child custody, property rights if not being the charge materials. 2) The contested divorce cases did not cover any lawsuit regarding the wives rights. Although the judge had the ex officio rights in determining the wives rights whether requested or not, the judges of Palopo Religious Court were just in case of the cause of divorce where the husband and wife were not willing to be divorced. So, the judges utilized their ex officio rights to punish the husbands for providing Mut'a according to their ability and feasibility. 3) In reconvenes decision, it was mentioned the wives rights in the judges decision in which they are Iddah living, Mut'ah, past living, and the child costs. At the living Iddah costs, it was decided by Palopo Religious Courts Palopo that it is not in the same nominal amount. It is also similar to the Mut'ah and children costs